The germination of perennial wall rocket (Diplotaxis tenuifolia [L.] DC.) and annual garden rocket (Eruca sativa Mill.) under controlled temperatures - Hall, Matthew; Jobling, Jenny; Rogers, Gordon (Plant Breeding and Seed Science, 2012)
The germination characteristics of three cultivars of perennial wall rocket and annual garden rocket were assessed at constant and diurnal temperatures for ten days. The seeds were exposed to constant temperatures of 5, 10, 15, 20, 25, 30 and 35°C or diurnal temperatures of 24/10, 28/16 and 18/5°C, with a 12/12 h exposure of each regime. The diurnal temperatures were chosen to reflect the minimum and maximum ambient temperatures experienced in Ellis Lane, Australia; during the spring, summer and winter. The total germination percentage (TGP) of perennial wall rocket was the highest at 20 to 30°C, whereas the highest TGP occurred at 10 to 30°C for annual garden rocket. The daily germination speed (DGS) and germination value (GV) are two useful formulas used to express the germination characteristics of seeds that under certain conditions do not achieve ≥50% germination. For both species, there was a significant interaction between the cultivar and temperature for the DGS and GV at both constant and diurnal temperatures; illustrating that the commercial cultivars of these species germinate at different rates in response to different ambient temperatures. This has important implications for the commercial production of these species, as cultivars with high germination rates need to be chosen for different seasonal conditions. At diurnal temperatures, there was an interaction between the cultivar and temperature for perennial wall rocket, with the cvs. DT1 and DT2 having similar TGPs across all of the temperature regimes, whereas the cv. DT3 had lower TGPs across all of the regimes. There was no interaction between the cultivar and diurnal temperature for annual garden rocket; however, temperature did influence the TGP, with higher values at 24/10 and 18/5°C. The germination of the smaller seeds from the perennial species was found to be more dependent on temperature than the larger seeds from the annual species. This is likely due to differences in stored reserves and the influence of secondary dormancy in the respective species.